Acceptability of a sustainable technological innovation applied to traditional soft cheese: Information concerning the benefits for health and the environment can compensate for a lower hedonic appreciation. (March 2023) - Martin, Christophe; Harel-Oger, Marielle; Garric, Gilles; Le Loir, Yves; Soler, Louis-Georges; Marette, Stéphan
Highlights: Liking and WTP for three cheeses, including two innovative ones, were measured. Information was given: nature of the process, health and environment benefits. Information about the new process did not change WTPs for the new cheeses. Increase in WTPs for the new cheese following health and environment information. Health and environment information compensated for a liking difference. Abstract: The objective of this work was to study the reaction of consumers to a technological innovation (a radically new manufacturing process) applied to a traditional product (cheese). A traditional cheese and two cheeses resulting from a new sustainable process were evaluated by 142 consumers. These cheeses were first evaluated blind, giving rise to liking score and willingness to pay (WTP). Following a message concerning the nature of the processes used for the three cheeses, the consumers gave their WTP once again. The last two stages of the protocol consisted of successively revealing two pieces of information concerning the benefits of the new process for health and the environment and in measuring, at each of these two stages, the WTP of the consumers. Blind tasting showed that the two new cheeses were less appreciated than the traditional cheese. The information concerning the nature of the processes used did not significantly influence the WTP of the new cheeses but caused a revaluation of the traditional cheese. Information on the benefits of the new process has reduced the gap between the WTP of the three cheeses by decreasing the WTP for the traditional cheese and increasing the WTP for the new cheeses. This information made it possible to compensate for differences in liking of 1 to 2 points on a scale of 10. However, there is heterogeneity in consumer reactions. Indeed, some consumers (23%) did not appreciate the sensory properties of the new cheeses, and despite the assimilation of the information concerning the benefits of the new process, their WTP remained lower than those of traditional cheese. These results show that there is no major opposition to the application of technological innovations to traditional products such as cheese and that information concerning health and environmental benefits is positively accepted.